Decolourization of synthetic dyes using free and immobilized Aspergillus species - Gnanadoss, J. Joel; Jebapriya, G. Roseline (Research in Biotechnology, 2013)
The aim of the present investigation was to study the biosorption and decolourization of congo red and erichrome black T by Aspergillus sp. (A. niger LCJ 1 and A. nidulans LCJ 2). Decolourization of both the dyes was determined on free and immobilized cell of Aspergillus sp. in culture media containing 25 mg/L of the respective dyes. The amount of decolourization was determined by monitoring the decrease in absorbance of each dye. Spectrophometric data revealed that, the maximum decolourization of congo red and erichrome black T was in immobilized mycelium of Aspergillus sp. on polyurethane foam (PUF). This study showed that fungal biomass (A. niger and A. nidulans) could effectively be used as an alternative to the conventional physico-chemical methods.Ã‚Â